Analysis of the Implementation of Total Quality Management (TQM) with the PDCA Method in Improving Product Quality before the Final Inspection Stage at PT Elektronik Indonesia - Gian Lucky Fernandhi; Hanifah Khalilah; Aldi Maulana; Sesarius Winson Gultom; Yudi Prastyo (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving product quality before the final inspection stage at PT.Indonesian ElectronicsThe main problem faced by the company is the high level of product defects that are only detected at the final inspection stage, resulting in increased rework costs, material waste, and reduced production process efficiency. The method used in this study is the Total Quality Management approach with the PDCA (Plan-Do-Check-Act) cycle supported by quality control tools such as Pareto diagrams, fishbone diagrams, and control charts. Research data was obtained from observations, interviews, and company production data before and after the implementation of improvements. The results showed that the dominant types of defects came from machining process errors, lack of operator work standardization, and suboptimal process supervision. After improvements were made through SOP standardization, operator training, and machine preventive maintenance, the product defect rate successfully decreased from 8.5% to 3.2%. The number of defective products also decreased from 300 units to 140 units, or a reduction of 160 defective units. This decrease had a significant financial impact on the company, especially in reducing rework costs by 40%. Based on the estimated rework cost of Rp25,000 per unit and the product value of Rp150,000 per unit, the company obtained a total saving cost of around Rp28,000,000 derived from reduced rework activities, reduced reject products, and increased number of saleable products. In addition to providing production cost savings, the implementation of TQM also increases operational efficiency and stability of the production process before the final inspection stage. The results of the study indicate that the systematic implementation of TQM through the PDCA approach is effective in controlling product quality from the beginning of the production process, reducing the level of defects, and providing economic benefits through continuous improvement in production cost efficiency.